A Review of Autoimmune Acquired von Willebrand Factor Deficiency in Japan - Ichinose, Akitada; Osaki, Tsukasa; Souri, Masayoshi; Favaloro, Emmanuel J (Seminars in thrombosis and hemostasis, 2022)
von Willebrand factor (VWF) forms high-molecular-weight multimers and plays an essential role in hemostasis, and thus its deficiency leads to bleeding symptoms. Acquired von Willebrand syndrome (AVWS) is rare, but potentially underdiagnosed, and develops in various underlying disorders. AVWS caused by anti-VWF autoantibodies is a rare subcategory of AVWS that can also be referred to as autoimmune VWF deficiency (AiVWFD). We performed a search of patients with autoimmune coagulation factor deficiencies in our nationwide survey in Japan. Among these, suspected cases of AiVWFD were extremely few, with only 11 case consultations in the last 10 years. Of these, three and five were respectively positive for anti-VWF autoantibodies (anti-VWF-Ab) and VWF inhibitor (VWF-inh). We also performed an extensive literature search of other cases from Japan, and in total, 40 cases were finally identified to have AiVWFD, with mean age of 55.0 years. Most underlying disorders were lympho- or myeloproliferative diseases, followed by autoimmune diseases. The major bleeding sites were subcutaneous and mucosal, the bleeding severity was moderate, and there were no hemorrhagic deaths. Bleeding time was prolonged; factor VIII activity, VWF antigen, and VWF activity were decreased, and high-molecular-weight VWF multimers were absent or decreased. These are similar to the common abnormal laboratory findings observed among general AVWS cases. Hemostatic therapy often involved VWF concentrates and vasopressin, and antibody eradication therapy often included corticosteroids and achieved remission. Notably, of all cases, 68% had anti-VWF-Abs, and 83% of anti-VWF-Ab-positive patients were also VWF-inh positive. To accumulate precise clinical information on AiVWFD, it is necessary to verify and improve the measurement methods for both anti-VWF-Ab and anti-VWF-inh. These findings from Japan should be confirmed in other geographic localities.von Willebrand factor (VWF) forms high-molecular-weight multimers and plays an essential role in hemostasis, and thus its deficiency leads to bleeding symptoms. Acquired von Willebrand syndrome (AVWS) is rare, but potentially underdiagnosed, and develops in various underlying disorders. AVWS caused by anti-VWF autoantibodies is a rare subcategory of AVWS that can also be referred to as autoimmune VWF deficiency (AiVWFD). We performed a search of patients with autoimmune coagulation factor deficiencies in our nationwide survey in Japan. Among these, suspected cases of AiVWFD were extremely few, with only 11 case consultations in the last 10 years. Of these, three and five were respectively positive for anti-VWF autoantibodies (anti-VWF-Ab) and VWF inhibitor (VWF-inh). We also performed an extensive literature search of other cases from Japan, and in total, 40 cases were finally identified to have AiVWFD, with mean age of 55.0 years. Most underlying disorders were lympho- or myeloproliferative diseases, followed by autoimmune diseases. The major bleeding sites were subcutaneous and mucosal, the bleeding severity was moderate, and there were no hemorrhagic deaths. Bleeding time was prolonged; factor VIII activity, VWF antigen, and VWF activity were decreased, and high-molecular-weight VWF multimers were absent or decreased. These are similar to the common abnormal laboratory findings observed among general AVWS cases. Hemostatic therapy often involved VWF concentrates and vasopressin, and antibody eradication therapy often included corticosteroids and achieved remission. Notably, of all cases, 68% had anti-VWF-Abs, and 83% of anti-VWF-Ab-positive patients were also VWF-inh positive. To accumulate precise clinical information on AiVWFD, it is necessary to verify and improve the measurement methods for both anti-VWF-Ab and anti-VWF-inh. These findings from Japan should be confirmed in other geographic localities.